O LIVRO DIDÁTICO PARA O ENSINO MÉDIO E A ESMAECIDA PRESENÇA DE ESCRITORAS BRASILEIRAS NEGRAS (Miscelânea: Journal of Literature and Social Life, 2024)
This article presents considerations about of two Portuguese language teaching collections from the National Book and Teaching Material Program (PNLD) for high school (2021) regarding the presence or absence of books by black Brazilian writers discussed in literature classes. This is a documentary analysis that reflects on three aspects: the teaching of literature from the perspective of literary literacy; the textbook in literature classes; the works of black women in teaching activities on Brazilian literature. A subtle and incomplete presence of the black women writers is evident, since their works, when present, are fragmented and do not provide opportunities for practices to expand students' literary literacy.